The Relations between the Texas Republic and Mexico: The Santa Fe Expedition - Kökény, Andrea (Acta Hispanica, 2020)
The Texan Santa Fe Expedition was a commercial and military enterprise. It was unofficially initiated by Mirabeau Buonaparte Lamar, second President of the Republic of Texas, in the summer of 1841. His aim was to gain control over the lucrative Santa Fe Trail and to establish Texas jurisdiction over the area. The expedition included twenty-one wagons carrying merchandise and was accompanied by businessmen, Lamar’s commissioners, and a military escort of some three hundred volunteers. The members of the expedition expected a warm welcome by the citizens of New Mexico, but instead, were “welcomed” by a detachment of the Mexican Army. The Texans, reduced in number and broken in health and spirit, were forced to surrender, and then to march 1,600 miles from Santa Fe to Mexico City. They were held prisoners for almost a year and released only in the spring of 1842. In my paper I propose to discuss the organization, course, and consequences of the ill-fated expedition. My most important primary sources will be the official documents and the diplomatic correspondence of the Republic of Texas, the correspondence and addresses of President Mirabeau Buonaparte Lamar, and the accounts of the participants of the Santa Fe expedition.